The mediating role of perceived value on the relationship between service quality and customer service loyalty: An explanatory study for Iraqi private banking sector - Al Chalabi, Hussein Sabah Abdulhasan (My University, 2017)
Customer service loyalty is one of the crucial construct explained with different concepts in the literature. The aim of the research is to deepen the understanding of the concepts of service quality, perceived value, and customer service loyalty. In addition, evaluating the concepts of service quality and perceived value which explain customer service loyalty on the Iraq sampling frame is another aim of the present study. So, service loyalty, value and service quality perception of customers is within the scope of the present research. The researcher selected the Iraqi Middle East Investment Bank and the Commercial Bank of Iraq in Baghdad Province that are working in an unstable security context to coduct his research since such studies have not been much conducted in similar circumstances such as that of Iraq. The total sample size was 250 individuals. A questionnaire relating to the whole dimensions adapted from the reliable and valid scales in the literature to measure service quality, perceived value and service loyalty. The research determined hypotheses which were tested correlation, simple regression, hierarchical regression analysis and T-test as well as F-test after the controlling validity and reliability of the scales via Cronbach Alpha values and factor analyses. The results of analyses indicated there were significant correlation between service quality, perceived value and service loyalty. The research reached a set of conclusions which was the most important one was that perceived value variable played a mediating role between the relationship of service quality and customer service loyalty. In addition, some differences were found service quality, perceived value, and service loyalty in terms of demographic characteristics.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2017
Keywords: Service quality; Perceived value; Customer service loyalty; SERVPERF